2015
DOI: 10.1038/srep18271
|View full text |Cite
|
Sign up to set email alerts
|

Nudix hydrolases degrade protein-conjugated ADP-ribose

Abstract: ADP-ribosylation refers to the transfer of the ADP-ribose group from NAD+ to target proteins post-translationally, either attached singly as mono(ADP-ribose) (MAR) or in polymeric chains as poly(ADP-ribose) (PAR). Though ADP-ribosylation is therapeutically important, investigation of this protein modification has been limited by a lack of proteomic tools for site identification. Recent work has demonstrated the potential of a tag-based pipeline in which MAR/PAR is hydrolyzed down to phosphoribose, leaving a 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 50 publications
1
77
0
Order By: Relevance
“…The investigators showed that different NUDIX enzymes, including the RNA 5 ′ pyrophosphohydrolase (RppH) from Escherichia coli (EcRppH) and the human NUDIX enzyme HsNudT16, can be used for digestion of PAR chains for MS (Table 2). However, in a direct comparison with SVP, only two of the 14 phosphoribosylated peptides detected from automodified PARP-1 by Daniels et al (2015b) were found in all three enzyme-treated samples (SVP vs. EcRppH and HsNudT16). Palazzo et al (2015) detected only two distinct sites of ADP-ribosylation on PARP-1, but these sites overlapped those identified by Daniels et al (2015b).…”
Section: Chemical Cleavagementioning
confidence: 88%
See 4 more Smart Citations
“…The investigators showed that different NUDIX enzymes, including the RNA 5 ′ pyrophosphohydrolase (RppH) from Escherichia coli (EcRppH) and the human NUDIX enzyme HsNudT16, can be used for digestion of PAR chains for MS (Table 2). However, in a direct comparison with SVP, only two of the 14 phosphoribosylated peptides detected from automodified PARP-1 by Daniels et al (2015b) were found in all three enzyme-treated samples (SVP vs. EcRppH and HsNudT16). Palazzo et al (2015) detected only two distinct sites of ADP-ribosylation on PARP-1, but these sites overlapped those identified by Daniels et al (2015b).…”
Section: Chemical Cleavagementioning
confidence: 88%
“…a See Kalisch et al (2012), Feijs et al (2013), Krietsch et al (2013), Hottiger (2015), Teloni and Altmeyer (2016), and Rack et al (2016) as well as references therein for a more comprehensive listing of ARBDs. 2006), PAR glycohydrolase (PARG) (Slade et al 2011), TARG/C6orf130 (Sharifi et al 2013), MacroD1 and MacroD2 Rosenthal et al 2013), and the NUDIX family of hydrolases (Daniels et al 2015b). Many of these enzymes contain a macrodomain fold, which allows them to interact with ADP-ribosylated substrates.…”
Section: Adp-ribose and Par Hydrolases: Erasersmentioning
confidence: 99%
See 3 more Smart Citations